Generalized rational contractions endowed with a graph and an application to a system of integral equations - Isik, H.; Hussain N.; Kutbi M.A. (Eudoxus Press, LLC, 2017)
In the present paper, we introduce the notion of generalized rational contraction including admissible mappings and establish coincidence point and common fixed point results for this class of mappings defined on ordinary as well as ordered metric spaces. Our results extend, generalize and unify com- parable results in the existing literature. Applying these results, we deduce fixed point results on metric spaces endowed with graph. An example and application to obtain the existence of common solution for a system of integral equations are also given in order to illustrate the effectiveness of the offered results. © 2017 by Eudoxus Press, LLC, All rights reserved.
Keywords: Admissible mappings; Common fixed point; Integral equations; Point of coincidence; Rational contractions; Weakly compatible mappings